Diseño de un centro agrícola para el cantón Mira - Villarreal Rosero, Francisco Daniel (2024)
The “Design of an Agricultural Center for the Mira town” is the result of research in the social, economic, cultural, environmental, and agricultural sectors. Currently, agriculture is the main economic activity of the town with 58% of its EAP, however, the lack of infrastructure, scarce technical training and the excessive use of chemical products limit economic growth and aggravate the pollution of resources natural. The architectural project allows the learning of new cultivation techniques and the application of organic, ecological, and precision agriculture, with spaces and common areas that comprehensively promote the development of the Mira town